The Indonesian Economy from the Colonial Extraction Period until the Post-New Order Period: A Review of Thee Kian Wie’s Major Works - Maria Monica Wihardja; Siwage Dharma Negara (Economics and Finance in Indonesia, 2015)
This paper reviews some major works of Thee Kian Wie, one of Indonesia’s most distinguished economic historians, that spans from the Colonial period until the post-New Order period. His works emphasize that economic history can guide future economic policy. Current problems in Indonesia were resulted from past policy failures. Indonesia needs to consistently embark on open economic policies, free itself from "colonial period mentality". Investment should be made in rebuilding crumbling infrastructure, improving the quality of health and education services, and addressing poor law enforcement. If current corruption persists, Indonesia could not hope to become a dynamic and prosperous country.